Anatomy of the lymph node venous networks of the groin and their investigation by ultrasonography. (June 2016) - Uhl, Jean Francois; Lo Vuolo, Miguel; Labropoulos, Nicos
Objective: To describe the anatomy of the lymph node venous networks of the groin and their assessment by ultrasonography. Material and methods: Anatomical dissection of 400 limbs in 200 fresh cadavers following latex injection as well as analysis of 100 CT venograms. Routine ultrasound examinations were done in patients with chronic venous disease. Results: Lymph node venous networks were found in either normal subjects or chronic venous disease patients with no history of operation. These networks have three main characteristics: they cross the nodes, are connected to the femoral vein by direct perforators, and join the great saphenous vein and/or anterior accessory great saphenous vein. After groin surgery, lymph node venous networks are commonly seen as a dilated and refluxing network with a dystrophic aspect. We found dilated lymph node venous networks in about 15% of the dissected cadavers. Conclusion: It is likely that lymph node venous networks represent remodeling and dystrophic changes of a normal pre-existing network rather than neovessels related to angiogenic factors that occur as a result of an inflammatory response to surgery. The so-called neovascularization after surgery could, in a number of cases, actually be the onset of dystrophic lymph node venous networks. Lymph node venous networks are an ever-present anatomical finding in the groin area. Their dilatation as well as the presence of reflux should be ruled out by US examination of the venous system as they represent a contraindication to a groin approach, particularly in recurrent varicose veins after surgery patients. A refluxing lymph node venous network should be treated by echo-guided foam injection.